FINANCIAL STATEMENT CONSOLIDATION METHODS UNDER INTERNATIONAL ACCOUNTING REGULATIONS - Milojević, Ivan; Stamenović, David (Veredas do Direito, 2026)
The concentration and internationalization of capital, together with the increasing interconnectedness of business entities, have created a growing need for the consolidation of financial statements. A significant portion of global capital is held within groups of related companies and this trend continues to intensify in modern economic systems. As business structures have become more complex, professional accounting regulations and standards have evolved in order to respond to the practical challenges faced by accountants, auditors and financial analysts. The development of international accounting standards has particularly contributed to improving the comparability, transparency and reliability of consolidated financial reporting across different jurisdictions. This paper analyzes the compliance of methods used for consolidating financial statements with international accounting regulations and examines their principal characteristics, advantages and limitations. Special attention is devoted to the relationship between consolidation methods and the degree of control or influence exercised within corporate groups. The paper also considers the extent to which specific consolidation methods correspond to the actual needs of national financial reporting frameworks and contemporary business practice.